PENGARUH PROPORSI BERAS SEJAHTERA DAN SAWUT SINGKONG TERHADAP MUTU NASI SAWUT: The Effect of Prosperous Rice and Shredded Cassava Proportion on the Quality of Shredded Cassava Rice - Wiwik Pratiwi; Baiq Rien Handayani; Nazaruddin Nazaruddin (Pro Food, 2020)
ABSTRACT The purpose of this study was to determine the effect of proportion of “Rastra” (Prosperous Rice) and shredded cassava on the quality of shredded cassava rice. The method used was experimental method in laboratory and designed using Randomized Block Design (RBD) with a single factor i.e. proportion of prosperous rice and shredded cassava. The treatments of rice and shredded cassava proportions were consisted of 100%: 0%; 80%: 20%; 60%: 40%; 40%: 60% and 20%: 80%. Chemical and organoleptic data were analyzed using analysis of variance (ANOVA) at 5% significance level using Co-stat software. The significant difference data were tested by a real difference test with honestly significant difference test, while the microbiological data were analyzed with a descriptive method. The results showed that the proportion of prosperous rice and shredded cassava had a significantly different effect on chemical quality (moisture content and ash content) and organoleptic quality (color, taste and texture) but did not significantly affect on organoleptic quality (aroma) and total microbes. 60% of prosperous rice and 40% of shredded cassava was recommended as the best proportion to produce shredded cassava rice with characteristic yellowish white, odorless smell, fluffy texture and taste of rice and has a water content of 66.02%, a value of 0.13% ash and microbiological quality that has met the SNI standard 7388: 2009 with a total microbe of 3.3x105 CFU / g, total mushroom 7,2x102 CFU / g and total coliform 27 MPN / g. Keywords: Prosperous Rice, Quality, Proportion, Shredded Cassava ABSTRAK Tujuan penelitian ini adalah untuk mengetahui pengaruh proporsi beras sejahtera dan sawut singkong terhadap komponen mutu nasi sawut. Metode yang digunakan dalam penelitian ini adalah metode eksperimental yang dilaksanakan di Laboratorium dan dirancang menggunakan Rancangan Acak Kelompok (RAK) dengan satu faktor yaitu proporsi beras sejahtera dan sawut (100%:0%; 80%:20%; 60%:40%; 40%:60% dan 20%:80%). Data hasil pengamatan kimia dan organoleptik dianalisis dengan analisis keragaman (ANOVA) pada taraf nyata 5% dengan menggunakan software Co-Stat dan diuji lanjut dengan BNJ, sedangkan data hasil pengamatan mikrobiologi dianalisis menggunakan metode deskriptif. Hasil penelitian menunjukkan bahwa proporsi beras sejahtera dan sawut singkong memberikan pengaruh yang berbeda nyata terhadap mutu kimia (kadar air dan kadar abu nasi) dan mutu organoleptik (warna, rasa dan tekstur) namun tidak berpengaruh nyata pada mutu organoleptik (aroma) dan mutu mikrobiologi (total mikroba). Perlakuan proporsi beras sejahtera dan sawut singkong (60%:40%) merupakan perlakuan terbaik karena menghasilkan nasi sawut dengan warna putih kekuningan, aroma tidak berbau apek, tekstur pule, berasa nasi serta memiliki kadar air 66,02%, nilai kadar abu 0,13% serta mutu mikrobiologi yang telah memenuhi standar SNI 7388:2009 dengan total mikroba 3,3x105 CFU/g, total jamur 7,2x102 CFU/g dan total koliform 27 MPN/g. Kata Kunci: Beras Sejahtera, Mutu, Proporsi, Sawut Singkong.